Radiative MHD Walter’s Liquid-B Flow Past a Semi-Infinite Vertical Plate in the Presence of Viscous Dissipation with a Heat Source - DAMALA, Chenna Kesavaiah; BHUMARAPU, Venkateswarlu; MAKINDE, Oluwole Daniel (Engineering Transactions, 2021)
The free convective magnetohydrodynamics (MHD) flow of a non-Newtonian fluid due to a semi-infinite vertical plate under the influence of radiation and viscous dissipation is investigated. The system of partial differential equations is derived and solved for the solutions of velocity and temperature profiles along with the Nusselt number and skin friction by using the perturbation technique. The related important dimensionless parameters of Eckert, Grashof, and Prandtl numbers, magnetic field, radiation and heat source are discussed and shown in graphs. Also, the Nusselt number and skin friction at the plate are obtained and presented in the tabular forms. Finally, the corresponding result of Newtonian fluid is obtained by setting viscoelastic parameter k1 = 0. It is worth mentioning that the obtained results coincide with the previously published results.